Jared Dillon: capstone - Dillon, Jared, artist (Colorado State University. Libraries, 2021)
The artist's statement: As a designer, I strive to communicate. To get a certain feeling across through the character of illustration and typography captures me to no end. Understanding all of that, one can create an entire story that leads a viewer seamlessly through its many twists and turns. I am interested in the full scope of this, as it lends itself to a physical object. From designing a logo, to constructing the physical containers, the entirety of the process informs itself as it goes along. Understanding and creating characters has always been something that I've done. They are the key to most stories and being able to bring them to life visually is something that'll interest me for the rest of my life. I work at characters like I do with anything else: fast and furious sketching. There's a million ways to go about designing anything, and I try a whole bunch of them to see what might work the best.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design